Assessing the acceptability and feasibility of remote spirometric monitoring for rural patients with interstitial lung disease: a multimethod approach - Ryan D. Boente; Sydney Schacht; Rebecca Borton; Joseph Vincent; Lilian Golzarri-Arroyo; Nicholas Rattray (Respiratory Research, 2024)
Abstract Introduction Interstitial lung disease encompasses a group of rare lung conditions causing inflammation and scarring of lung tissue. The typical method of monitoring disease activity is through pulmonary function tests performed in a hospital setting. However, accessing care can be difficult for rural patients due to numerous barriers. This study assesses the feasibility and acceptability of home spirometry telemonitoring using MIR-Spirometers and the patientMpower home-monitoring platform for rural patients with interstitial lung disease. Methods Unblinded, uncontrolled, prospective, multiple-methods study of the feasibility and utility of remote monitoring of 20 rural subjects with interstitial lung disease. Study assessments include adherence to twice weekly spirometry for 3 months in addition to mMRC dyspnea and EQ-5D-5L health-related quality of life questionnaires with each spirometry maneuver. Upon completion, subjects were encouraged to complete an 11-question satisfaction survey and participate in semi-structured qualitative interviews to further explore expectations and perceptions of rural patients to telehealth and remote patient monitoring. Results 19 subjects completed the 3-month study period. Adherence to twice weekly spirometry was mean 53% ± 38%, with participants on average performing 2.26 ± 1.69 maneuvers per week. The median (Range) number of maneuvers per week was 2.0 (0.0, 7.0). The majority of participants responded favorably to the patient satisfaction survey questions. Themes regarding barriers to access included: lack of local specialty care, distance to center with expertise, and time, distance, and high cost associated with travel. Remote monitoring was well perceived amongst subjects as a way to improve access and overcome barriers. Conclusions Remote spirometry monitoring through web-based telehealth is acceptable and feasible for rural patients. Perceived benefits include overcoming access barriers like time, distance, and travel costs. However, cost, reimbursement, and internet access must be addressed before implementing it widely. Future studies are needed to ensure long-term feasibility and to compare outcomes with usual care.